Single Crystal X-Ray Diffraction in Structure Elucidation of Arborinine from Glycosmis pentaphylla - Das, Moon M.; Deka, Dibakar Chandra; Thakuria, Ranjit (Natural Products Journal, The, 2017)
Background: Arborinine is a naturally found alkaloid with various biological activities. It has been isolated from the leaf extract of Glycosmis pentaphylla, a traditionally used medicinal plant of North East of India. Single crystal X-ray diffraction on arborinine has never been reported earlier. Objective: The main objective of the present study is to report the isolation and characterization of arborinine and its single crystal X-ray diffraction analysis. Method: Arborinine was isolated from the leaf extract of Glycosmis pentaphylla by repeated column chromatography. Fine yellow needle-shaped crystals were recovered from a solution of purified arborinine in a mixture of ethyl acetate and petroleum ether (1:5). The purified compound is characterized by IR, NMR, HRMS and single crystal X-ray diffraction. Results: The crystal structure was solved in orthorhombic Pbca space group with unit cell parameters a = 14.805(3) Å, b = 7.5342(15) Å, c = 23.620(5) Å, = 90°, β= 90°, γ= 90°, V= 2634.7(9) s, Φ#150; = 8, Dcalc = 1.438 Φ#156;gm-3 and F (000) = 1200. The molecules of arborinine with a planar acridine ring with flanking methoxy groups at 2- and 3- position dsplay a 3D framework resulting from weak C-H•••O, π-π stacking and Van der Waal interactions.i Conclusion: Single crystal X-ray diffraction on arborinine is reported for the first time. High field NMR and high resolution mass are also reported for the first time on a sample of arborinine isolated from the plant Glycosmis pentaphylla. æ#133;
Keywords: Rutaceae